Changing Ethnic Diversity in Peninsular Malaysia - Hans-Dieter Evers (Kajian Malaysia, 2014)
This paper reviews several approaches for measuring and evaluating ethnic diversity. Based on Simpson's diversity index, a metric commonly used in biodiversity research, an "ethnic diversity index" (EDI) is developed that describes the degree of variety of ethnic groups living together on a common territory. The EDI values of the states of Peninsular Malaysia and Kuala Lumpur reveal a general decrease in ethnic diversity between 1970 and 2000. This change is attributed to migration, government policy and urban planning. Ashby's "Law of Requisite Variety" and Ostrom's recommendation for the governance of biodiversity are used to address problems associated with the governance of complex and highly diverse social systems.